Private Sector Development in Conflict Regions : Viable Support Options in the West Bank and Gaza - Nasir, John; Al-Muthaffar, Ranan; Kacem, Rimal (World Bank, Washington, DC, 2012)
As a result of the extensive security restrictions, growth in the West Bank and Gaza in the past has become dependent on aid contributions through the Palestinian Authority (PA). However, sustainable and inclusive growth requires a strong private sector capable of absorbing a growing labor force. Consequently, the World Bank in partnership with the UK's Department for International Development (DFID) developed the Palestinian Facility for New Market Development (FNMD). This matching grant scheme was designed to reduce the risk of investing in the highly uncertain environment and encourage enterprises to upgrade their capabilities, develop new products and enter new markets. This Quick Note provides an overview of the design and outcomes of FNMD and highlights the lessons learned in implementing the project. Lessons learned from this initiative underline that there are viable private sector options, even in fragile environments such as Gaza.